Mediation as a Conflict-Solving Device in Collective Industrial Disputes - Keller, Berndt (Relations industrielles / Industrial Relations, 1988)
This paper is an attempt to schematize and survey those recent efforts of industrial relationists and labor economists to examine mediation within an inter-disciplinary framework.